Crop and medicinal plants proteomics in response to salt stress - Aghaei, Keyvan; Komatsu, Setsuko (Frontiers in Plant Science, 2013)
Increasing of world population marks a serious need to create new crop cultivars and medicinal plants with high growth and production at any environmental situations. Among the environmental unfavorable conditions, salinity is the most widespread in the world. Crop production and growth severely decreases under salt stress; however, some crop cultivars show significant tolerance against the negative effects of salinity. Among salt stress responses of crops, proteomic responses play a pivotal role in their ability to cope with it and have become the main center of notification. Many physiological responses are detectable in terms of protein increase and decrease even before physiological responses take place. Thus proteomic approach makes a short cut in the way of inferring how crops response to salt stress. Nowadays many salt-responsive proteins such as heat shock proteins, pathogen related proteins, protein kinases, ascorbate peroxidase, osmotin, ornithine decarboxylase and some transcription factors, have been detected in some major crops which are thought to give them the ability of withstanding against salt stress. Proteomic analysis of medicinal plants also revealed that alkaloid biosynthesis related proteins such as tryptophan synthase, codeinone reductase, strictosidine synthase and 12-oxophytodienoate reductase might have major role in production of secondary metabolites. In this review we are comparing some different or similar proteomic responses of several crops and medicinal plants to salt stress and discuss about the future prospects.